Investigating the relationship between monetary rewards and flexible work schedule on intention to stay in ICT companies - Mohd Zin, Md Lazim; Pangil, Faizuniah; Othman, Siti Zubaidah (Journal of Business Management and Accounting, 2012)
Retaining existing employees, especially the skilled information technology (IT) employees is becoming more important due to business growth, imbalance between demand and supply, and high turnover rate. The paper seeks to investigate the relationship between rewards and flexible work schedule on intention to stay among professional IT employees. The two factors investigated in this study are monetary rewards (salary and bonus) and flexible work schedule. Results from 178 participants indicate that both monetary rewards (salary and bonus) and flexible work schedule were significantly positively related to intention to stay. Though salary, bonus and flexible work schedule indicate significant positive relationship with intention to stay, salary makes the strongest contribution to intention to stay. Implications of the findings, potential limitations of the study, and directions for future research are suggested
Keywords: Monetary rewards; flexible work schedule; intention to stay; information technology workers